Biofortification of Spring Barley Grain with Microelements through Sulfur Fertilization - Bożena Barczak; Magdalena Jastrzębska; Marta K. Kostrzewska (Journal of Chemistry)
One means of enriching plants with microelements is agronomic biofortification, whereby the mineral composition of plants is stimulated through appropriate fertilization. A fertilizer component which has received much attention in recent years is sulphur. Due to the significant reduction in SO2 emissions from industrial sources to the atmosphere, a progressive deficiency of this nutrient has been observed in soils in Poland and other parts of the world. Therefore, a study was undertaken to assess the effect of different application rates (20 and 40 kg·ha−1) and forms (elemental and ionic) of sulphur on the content of selected micronutrients (Mn, Fe, Zn, and Cu) and their proportions (Fe : Mn) in the grain of the Antek variety of spring barley. In a three-year single-factor field experiment setup on luvisols with low content of sulphur, the following fertilizers were tested: ammonium sulphate, potassium sulphate, and Wigor S (80% elemental sulphur and 20% bentonite). It was demonstrated that, in the fertilization of spring barley, supplementation of NPK with sulphur can be regarded as an agronobmic method of biofortification of grain with micronutrients because it beneficially affects the content of manganese, iron, zinc, and copper in the grain. An increase in the content of these micronutrients was found in the grain of plants fertilized with sulphur in comparison to plants that were not fertilized with this nutrient in each of the growing seasons. Ammonium sulphate, compared to the other fertilizers tested, had the greatest impact on the content and uptake of all micronutrients, with the exception of zinc. Marked differences in the effect of the application rates of 20 and 40 kg·S·ha−1 were observed only for fertilizers containing the ionic form of sulphur. The beneficial effect of sulphur on the biofortification of microelements in spring barley grain indicates the need to include this nutrient in cultivation of this species.